3y-6x=4

Simple and best practice solution for 3y-6x=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y-6x=4 equation:


Simplifying
3y + -6x = 4

Reorder the terms:
-6x + 3y = 4

Solving
-6x + 3y = 4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3y' to each side of the equation.
-6x + 3y + -3y = 4 + -3y

Combine like terms: 3y + -3y = 0
-6x + 0 = 4 + -3y
-6x = 4 + -3y

Divide each side by '-6'.
x = -0.6666666667 + 0.5y

Simplifying
x = -0.6666666667 + 0.5y

See similar equations:

| (3*4)*(8-2)*3= | | forx=8 | | 3/7q-9/7q | | 14+12-(2*4*2)= | | 8=k+9 | | 12z-6/2 | | 10+6a=60-4b | | 7-(2*2)+2= | | 3(a-4)=27 | | 4.6+(-1.6)= | | 5*(12+3)+2+7= | | (5u+6)(9+u)=0 | | 6+24+(4+8)*8-4= | | 10-(3*2)+2+15= | | 64x^6-729y^12=0 | | x^2-y+ln(y+1)+c=0 | | Cos(2x-(pi/12))=sqrt2/2 | | 4x+28+7x=-9+54-6 | | 12+(6*5)-18= | | (0,-3);m=-2/3 | | 81z^3-24=0 | | 16-(-2x-4)-(5x-3x+2)=-4-(-8x+2) | | 3sin(5x)=2 | | y-ln(y+1)=x^2+c | | 5x-8x-1=3x-2+7 | | 2(y+2)=-3(2y-6)-5 | | ((9s^3)/(8t))/((9s^2)/(2t^2)) | | (9s^3/8t)/(9s^2/2t^2) | | 4x^2+4x-52=0 | | X+1.5x=69 | | x+2y=155 | | -3(2x-4)+2x=-(x-3)+12 |

Equations solver categories